Effects of replacement noug seed cake (Guizotia abyssinica) with treated tagasaste (Chamaecytisus palmensis) leaf meal on egg quality traits of layer hens - Amare Sisay Sendekie; Habtamu Ayalew Kasahun; Yohannes Dagnew Alemayhu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Egg quality treats are significantly impacted by nutritional factors either deficient or excessive quantities in the layer diets. In this study one hundred eight, 32 weeks age of Bovans Brown chickens were used as an experimental animals. Four iso-nitrogenous and iso-caloric based ration diets were formulated. The level of ration replacing NSC by TTLM was at 0%(T1), 5%(T2), 10%(T3) and 15%(T4) from the total ration. Complete Randomized Design (CRD) was used with four treatments, three replicate (9chicken/replicate) and the experiment lasted for 12 weeks. Egg quality parameters were determined at the interval 28 days by randomly taking 5 freshly-laid eggs from each replication and determine egg size, eggshell, albumen and yolk quality by using different measurement parameters. The results showed that egg shape index, yolk weight (g) and yolk ratio (%) were similar (P>0.05) among treatment groups. Eggshell thickness and yolk color score were significantly varied (p<0.05) with different levels of TTLM substitution. In the present study shell thickness, shell weight and shell ratio were higher in the treatment groups (5, 10 and 15% TTLM) than the control (0%) diets. The study showed that shell thickness ranged from 0.32-0.38 mm at T1 and T3 TTLM, respectively. Haugh unit (84.04±1.79) and albumen height (7.01±0.23) were highest (P<0.05) at T3 than the other treatments. Based on results most of the external and internal egg quality parameters were significantly changed when the level of TTLM increased up to15% than the control diet and it implies a great opportunity in utilizing TTLM.